2013
DOI: 10.1371/journal.ppat.1003244
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Hepatitis C Virus Cell Entry with Occludin Directed Blocking Antibodies

Abstract: Hepatitis C virus (HCV) is a major cause of liver disease worldwide. A better understanding of its life cycle, including the process of host cell entry, is important for the development of HCV therapies and model systems. Based on the requirement for numerous host factors, including the two tight junction proteins claudin-1 (CLDN1) and occludin (OCLN), HCV cell entry has been proposed to be a multi-step process. The lack of OCLN-specific inhibitors has prevented a comprehensive analysis of this process. To stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 50 publications
6
63
0
1
Order By: Relevance
“…Indeed, Sourisseau et al 35) reported that various FLAG-tag-inserted OCLN constructs were expressed in human renal carcinoma 786-O cells, which are normally not able to support HCV entry owing to insufficient OCLN expression, 8) and that HCVpp entry into cells, mediated by some of the constructs, was inhibited by anti-FLAG antibodies. Previously, we have successfully developed, using a differential screening strategy for parental Huh7.5.1 cells and Huh7.5.1-derived CLDN1-knockout S7-A cells, anti-CLDN1 monoclonal antibodies that markedly inhibited HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Sourisseau et al 35) reported that various FLAG-tag-inserted OCLN constructs were expressed in human renal carcinoma 786-O cells, which are normally not able to support HCV entry owing to insufficient OCLN expression, 8) and that HCVpp entry into cells, mediated by some of the constructs, was inhibited by anti-FLAG antibodies. Previously, we have successfully developed, using a differential screening strategy for parental Huh7.5.1 cells and Huh7.5.1-derived CLDN1-knockout S7-A cells, anti-CLDN1 monoclonal antibodies that markedly inhibited HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are many other examples of viruses that use different mechanisms for attachment and entry, including mammalian reovirus and human papillomavirus type 16 (HPV16) (54,58,59). Mammalian reovirus directly interacts with cell surface carbohydrate receptors and junctional adhesion molecule A (JAM-A) to direct attachment, and ␤1-integrins direct viral entry but do not function in viral attachment (54,60).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that the cellular protein apolipoprotein E (apoE) is incorporated on the HCV envelope and mediates virion attachment to target cells by binding to the cell surface HSPGs, mainly the syndecan-1 (SDC1) proteoglycan (18)(19)(20). HCV E2 interacts with other cell surface receptors/ coreceptors, such as CD81, claudin, occludin, SR-BI, and LDLR, which all play crucial roles in HCV cell entry at postattachment steps (21)(22)(23)(24)(25)(26)(27)(28). Additionally, several other cellular proteins and pathways were found to be important for efficient HCV infection in cell culture, including epidermal growth factor receptor (EGFR), EphA2, Niemann-Pick C1 (NPC1L1), phosphatidylinositol 3-kinase (PI3K)-Akt, and CIDEB (29)(30)(31)(32).…”
mentioning
confidence: 99%